2016
DOI: 10.3389/fpsyg.2016.00197
|View full text |Cite
|
Sign up to set email alerts
|

Standing in Your Peer’s Shoes Hurts Your Feats: The Self-Others Discrepancy in Risk Attitude and Impulsivity

Abstract: It is often a good strategy to “stand in the other person’s shoes” to see a situation from a different perspective. People frequently attempt to infer what someone else would recommend when no advisor is available to help with a decision. Such situations commonly concern intertemporal or risky choices, and the usual assumption is that lay people make such decisions differently than experts do. The aim of our study was to determine what intertemporal and risky decisions people make when they take their own pers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 37 publications
(60 reference statements)
1
8
0
1
Order By: Relevance
“…Recently, a new line of research has emerged which examines decisions affected by these two dimensions by placing social distance manipulations within a delay discounting context (e.g., "Would you choose to receive $100 now or $500 in a year for your cousin?"). A key goal of this research has been to compare the choices about delayed reinforcers people make for themselves to those they make for other people (Albrecht, Volz, Sutter, Laibson, & von Cramon, 2011;Bialaszek, Bakun, McGoun, & Zielonka, 2016;Kim, Schnall, & White, 2013;O'Connell, Christakou, Haffey, & Chakrabarti, 2013;Pronin, Olivola, & Kennedy, 2008;Ziegler & Tunney, 2012). In general, participants' choices for themselves and others are more similar when the participant feels closer to the person they are deciding for (c.f., Bialaszek et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, a new line of research has emerged which examines decisions affected by these two dimensions by placing social distance manipulations within a delay discounting context (e.g., "Would you choose to receive $100 now or $500 in a year for your cousin?"). A key goal of this research has been to compare the choices about delayed reinforcers people make for themselves to those they make for other people (Albrecht, Volz, Sutter, Laibson, & von Cramon, 2011;Bialaszek, Bakun, McGoun, & Zielonka, 2016;Kim, Schnall, & White, 2013;O'Connell, Christakou, Haffey, & Chakrabarti, 2013;Pronin, Olivola, & Kennedy, 2008;Ziegler & Tunney, 2012). In general, participants' choices for themselves and others are more similar when the participant feels closer to the person they are deciding for (c.f., Bialaszek et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…A key goal of this research has been to compare the choices about delayed reinforcers people make for themselves to those they make for other people (Albrecht, Volz, Sutter, Laibson, & von Cramon, 2011;Bialaszek, Bakun, McGoun, & Zielonka, 2016;Kim, Schnall, & White, 2013;O'Connell, Christakou, Haffey, & Chakrabarti, 2013;Pronin, Olivola, & Kennedy, 2008;Ziegler & Tunney, 2012). In general, participants' choices for themselves and others are more similar when the participant feels closer to the person they are deciding for (c.f., Bialaszek et al, 2016). As social distance increases, however, so does the difference in findings.…”
Section: Introductionmentioning
confidence: 99%
“…Results showed that the direction effect was significantly reduced. Taking the perspective of an expert also had an effect on discounting with people becoming more risk averse and more patient (Białek & Sawicki, 2014), while "standing in peer's shoes" resulted in increased risk seeking and impatience (Białaszek, Bakun, McGoun, & Zielonka, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The reference points can be imposed externally or have internal origins, and can be made explicitly by instruction, or more subtle, i.e. by priming (Israel, Rosenboim, & Shavit, 2014), perspective taking (Bialek & Sawicki, 2014;Białaszek, Bakun, McGoun, & Zielonka, 2016) or slight changes to the experimental procedure (Sawicki & Białek, 2016).…”
Section: Intertemporal Choicesmentioning
confidence: 99%
“…instrukcję. Ludzie wykazują mniejszą impulsywność, gdy pytani są o wyobrażenie sobie, co na ich miejscu zrobiłby ekspert (Białek, Sawicki, 2014), natomiast więk-szą, gdy wyobrażają sobie, jak postapiłby na ich miejscu laik (Białaszek, Bakun, McGoun, Zielonka, 2016). Ponadto ludzie przywiązują się do (choćby nieumyślnie) narzuconego punktu odniesienia.…”
Section: Czynniki Wpływające Na Siłę Dyskontowaniaunclassified